2020
DOI: 10.1097/tp.0000000000003323
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Analysis of Kidney Graft Viability Using 31P Magnetic Resonance Imaging Spectroscopy

Abstract: Background. The lack of organs for kidney transplantation is a growing concern. Expansion in organ supply has been proposed through the use of organs after circulatory death (donation after circulatory death [DCD]). However, many DCD grafts are discarded because of long warm ischemia times, and the absence of reliable measure of kidney viability. 31P magnetic resonance imaging (pMRI) spectroscopy is a noninvasive method to detect high-energy phosphate metabolites, such as ATP. Thus, pMRI could pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…A second tool to advance pretransplant kidney viability assessment during NMP is through innovative imaging methods. 11,[135][136][137] Near-infrared spectroscopy, (functional) MRI ([f]MRI), positron emission tomography, contrast-enhanced ultrasound, ultrafast ultrasound imaging, laser speckle imaging, and multiphoton microscopy imaging all have the potential to unravel renal physiological processes during NMP in a noninvasive manner (Table 3). Additionally, these methods may provide more information about regional differences in the functional properties of the ex vivo perfused kidney.…”
Section: Mpm Imagingmentioning
confidence: 99%
“…A second tool to advance pretransplant kidney viability assessment during NMP is through innovative imaging methods. 11,[135][136][137] Near-infrared spectroscopy, (functional) MRI ([f]MRI), positron emission tomography, contrast-enhanced ultrasound, ultrafast ultrasound imaging, laser speckle imaging, and multiphoton microscopy imaging all have the potential to unravel renal physiological processes during NMP in a noninvasive manner (Table 3). Additionally, these methods may provide more information about regional differences in the functional properties of the ex vivo perfused kidney.…”
Section: Mpm Imagingmentioning
confidence: 99%
“…Moreover, they found that ATP levels and cortical and medullary gadolinium elimination were inversely correlated with the severity of kidney histological injury. Thus, the measured parameters may be considered as biomarkers of kidney injury after warm ischemia, and Longchamp et al's method provides an innovative non-invasive approach to assessing kidney viability prior to transplantation [118].…”
Section: New Solutions In Perfusion Controlmentioning
confidence: 99%
“…Various molecular mechanisms are active in ischemia reperfusion injury. There is the critical role of the anaerobic metabolism during ischemia, resulting in intracellular acidosis, ATP depletion, and failure of ion-exchange channels, setting the stage for reperfusion injury ( 15 ). Post-reperfusion, innate and adaptive immune responses are activated by reactive oxygen species and damage associated molecular patterns, resulting in a sterile inflammation ( 16 19 ).…”
Section: Kidneymentioning
confidence: 99%